Catalytic performance and hydrothermal durability of CeO2-V2O5-ZrO2/WO3-TiO2 based NH3-SCR catalysts - Wang, Xinquan; Shi, Anju; Duan, Yingfeng; Wang, Jun; Shen, Meiqing (Catalysis science & technology, 2012)
Ceria modified V 2 O 5 -ZrO 2 /WO 3 -TiO 2 catalysts with different Ce loading (0, 5, 10 wt%) have been evaluated in the NH 3 -SCR process before and after hydrothermal aging (750 °C, 10 wt% H 2 O/air for 12 h). Compared with only Zr containing catalysts, addition of Ce greatly enhances the low temperature activity of the fresh catalyst, but it deactivates obviously after aging. The catalysts were characterized by XRD, XPS, H 2 -TPR and DRIFTS. The results suggest that not only the enrichment of Ce 3+ and the increased redox properties, but also the more active adsorbed nitrates on CeO 2 modified catalysts benefit the SCR reaction. The catalyst deactivation after aging is mainly due to the sintering and segregation of CeO 2 on the catalysts surface, suggesting the poor hydrothermal stability of the Ce component. However, additional provided NO 2 will compensate for the activity loss due to hydrothermal aging and significantly improve the low temperature SCR activity, suggesting a high NO 2 sensitivity of the Ce component. Moreover, it was found that a ceria, zirconia containing catalyst exhibits superior SCR activities, with both the fresh and aged 1%V 2 O 5 -10%CeO 2 -10%ZrO 2 /WO 3 -TiO 2 catalysts showing high NO x conversions (>95%) and selectivity to N 2 (>98%) in a wide temperature range of 200-500 °C, at a space velocity of 120 000 h −1 in a simulated exhaust containing 500 ppm NO x (NO 2 /NO = 1) and 5% H 2 O. Hydrothermally aged ceria, zirconia containing V 2 O 5 /WO 3 -TiO 2 catalysts exhibit superior SCR activities in NO 2 and H 2 O containing exhaust gases.